Exploration and Mapping of Methods for Researching Second Language Classrooms: Content Analysis based on Rod Ellis' book - Syarifaturrahmatullah, Syarifaturrahmatullah; Ahmad Fadhel Syakir Hidayat; Adamu Abubakar Muhammad; Afrah Masood; Mowafg Masuwd (El-Syaker : Samarinda International Journal of Language Studies, 2025)
Many researchers in the second language field face the challenge of choosing the right method for their research, often relying on one method for their various studies. This study aims to explore various research methods in the context of the second language classroom by conducting a content analysis based on a book by Rod Ellis. This research is qualitative and is conducted through a literature study, the analysis uses Krippendorff's content analysis method, which includes six stages: unitizing, sampling, recording, reducing, inferring, and narrating. The research findings show that Ellis categorizes research methods into two main categories: formal and practical. Formal research includes experimental, descriptive, and hybrid, theory-driven research. While practical research involves action and exploratory, practitioner research does not stem from theory but from teachers' desire to experiment with innovations in their classrooms.